Manajemen Oral Care pada Pasien Dengan Mechanical Ventilation di Intensive Care Unit: a Scoping Review - Daud Palo; Ayu Prawesti; Ristina Mirwanti (Universitas Malahayati, 2026)
ABSTRACT The use of mechanical ventilation causes oral disorders in patients, such as xerostomia, increased dental plaque, mucociliary dysfunction, and changes in oral flora composition. These conditions have the potential to cause colonization of pathogenic bacteria that cause Ventilator-Associated Pneumonia (VAP). Oral care interventions have been implemented as a preventive strategy, but scientific evidence related to oral care management is still limited, requiring further exploration. To explore the available literature on oral care management in patients with mechanical ventilation in intensive care units. The scoping review framework from Arksey and O'Malley was used to guide the review process, and the PRISMA-ScR checklist was used to report this scoping review. The databases used were PubMed, Scopus, CINAHL, ScienceDirect, and Google Scholar, from January 2014 to December 2024. Thematic analysis was applied to identify key findings in the literature. Ten eligible articles were included. Three main themes were identified: oral care protocols (assessment and frequency of oral care, implementation of oral care, use of antiseptics, mechanical cleaning methods, and additional oral care methods), measurement tools used to evaluate oral care, and the implications of oral care on clinical outcomes. Recommended oral care management includes assessing oral health using the Beck Oral Assessment Scale (BOAS) to determine the frequency of oral care, brushing teeth with a soft toothbrush, using 2% chlorhexidine antiseptic, suction, and administering oral moisturizers. Additional interventions include maintaining ETT cuff pressure at 20-25 cmH₂O, positioning the head of the bed at 30°, and subglottic suction to avoid the risk of aspiration. BOAS is the most widely used measurement tool for assessing patients' oral health. Oral care management not only reduces the incidence of VAP, but also reduces the duration of MV, length of ICU stay, mortality rate, and improves physiological parameters. Keywords: ICU, Oral Care, Mechanical Ventilation, Ventilator-Associated Pneumonia. ABSTRAK Penggunaan ventilasi mekanik menyebabkan gangguan pada mulut pasien seperti xerotomia, peningkatan plak gigi, disfungsi mukosiliari, dan perubahan komposisi flora mulut. Hal tersebut berpotensi menyebabkan kolonisasi bakteri patogen penyebab Ventilator-Associated Pneumonia (VAP). Intervensi oral care telah diimplementasikan sebagai strategi pencegahan, namun bukti ilmiah terkait manajemen oral care masih terbatas sehingga memerlukan eksplorasi lebih lanjut. Untuk mengeksplorasi literatur yang tersedia tentang manajemen oral care pada pasien dengan ventilasi mekanik di unit perawatan intensif. Kerangka kerja scoping review dari Arksey dan O'Malley digunakan untuk memandu proses tinjauan dan daftar periksa PRISMA-ScR digunakan untuk melaporkan tinjauan ruang lingkup ini. Basis data yang digunakan adalah PubMed, Scopus, CINAHL, ScienceDirect, dan Google Scholar, dari januari 2014 hingga Desember 2024. Analisis tematik diterapkan untuk mengidentifikasi temuan utama dalam literatur. Sepuluh artikel yang memenuhi syarat disertakan. Tiga tema utama teridentifikasi yaitu protokol oral care (penilaian dan frekuensi oral care, penerapan oral care, penggunaan antiseptik, metode pembersihan mekanis, dan metode tambahan oral care), alat ukur yang digunakan untuk mengevaluasi oral care, dan implikasi oral care terhadap hasil klinis.Manajemen oral care yang direkomendasikan meliputi penilaian kesehatan mulut menggunakan Beck Oral Assessment Scale (BOAS) untuk menentukan frekuensi oral care, penyikatan gigi dengan sikat gigi lembut, menggunakan antiseptik chlorhexidine 2%, suction, dan pemberian pelembab mulut. Intervensi tambahan dengan mempertahankan tekanan cuff ETT 20-25 cmH₂O, posisi Head of Bed 30°, dan suction subglotik untuk menghindari risiko aspirasi. BOAS merupakan alat ukur yang paling banyak digunakan untuk menilai kesehatan mulut pasien. Manajemen oral care tidak hanya menurunkan insiden VAP, tetapi juga mengurangi durasi MV, lama rawat ICU, angka mortalitas, serta memperbaiki parameter fisiologis. Kata Kunci: ICU, Oral Care, Mechanical Ventilation, Ventilator-Associated Pneumonia.